The role of negative politeness in power relations and character formation in online classrooms - Afriana; Ahmad, Salawati; Azwani Mohamed, Mimi Nahariah (Journal of Islamic, Social, Economics and Development, 2025)
This study explores the role of negative politeness in shaping power relations and fostering character development within online classroom interactions at a university in Batam, Indonesia. Drawing on Brown and Levinson’s (1987) politeness theory and a pragmatic approach, the research investigates how students and lecturers use politeness strategies to navigate hierarchical relationships in three English online courses. Data were obtained from transcribed online classroom interactions and semi-structured interviews with ten students, selected through purposive sampling. The findings reveal that negative politeness strategies particularly deference, hedging, and indirectness are frequently employed by students to acknowledge institutional power, maintain respect, and minimize imposition in communication. Lecturers’ use of formal and directive expressions further reinforces academic authority and social hierarchy. Over time, students demonstrate adaptive pragmatic awareness by consistently adjusting their linguistic behavior to align with the expectations of formal discourse. These strategies not only sustain harmonious interaction but also reflect the internalization of moral and social values. Interpreted through the lens of the Character Education Framework (Kemdikbud, 2010), the results show that the use of negative politeness promotes core virtues such as respect, integrity, responsibility, and self-control. Overall, this study highlights that politeness in online academic communication functions not only as a linguistic strategy to manage power but also as a means of cultivating ethical and character-based communication competence among students.